Assessing medical students’ attitudes, performance, and usage of ChatGPT in Jeddah, Saudi Arabia - Alammari, Dalia; Alamari, Elaf; Alamri, Rawan; Alharbi, Raneem; Felimban, Jumana; Aljohani, Jana (Frontiers in Artificial Intelligence, 2025)
BackgroundChatGPT, an advanced AI language model, has the potential to significantly enhance medical education by supporting clinical decision-making, facilitating knowledge acquisition, and improving learning outcomes. However, there remains a gap in understanding the risks and concerns surrounding the use of ChatGPT, as well as its impact on the quality of medical education in Jeddah, Saudi Arabia. This study investigates the role of ChatGPT in local medical education, offering insights into medical students’ attitudes and performance concerning the integration of AI into the medical curriculum.MethodsThis cross-sectional study was conducted from March to May 2024. It was approved by the institutional review board. An online survey was distributed to medical students in Jeddah to collect data on their awareness of ChatGPT and its impact on their attitudes and performance. The survey, which included 28 items across 2 sections was developed. For data analysis, Statistical Package for Social Sciences (SPSS) software (version 27.0) was used to conduct statistical analysis.ResultsThe final sample comprised 420 participants, of whom 84.3% had heard of ChatGPT, while 74.9% had used it prior to the study. The majority of participants were aged 18–21 (50.5%). Higher GPA and academic progression were significantly associated with greater awareness and performance related to ChatGPT. Additionally, privacy concerns, willingness to incorporate ChatGPT into learning and research, and perceptions of its ease of use were significantly correlated, with a p-value < 0.05.ConclusionThe findings indicate a generally positive perception of ChatGPT among medical students, particularly as they progress in their studies. Associations were observed between ChatGPT usage and students’ academic standing and attitudes toward AI. While the ease of use was appreciated, concerns regarding privacy, ethical implications, and data security were also prominent, reflecting global trends. Further longitudinal and experimental research is necessary to better understand the educational implications of ChatGPT and to ensure its responsible integration into medical curricula.